EFFECT OF PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION STRECHING WHEN COOLING DOWN SESSION ON RANGE OF MOTION OF EAST JAVA BANK JUNIOR VOLLEYBALL PLAYER - nurrochman, adi; Bawono, Mokhammad Nur (Jurnal Kesehatan Olahraga, 2019)
Background: Moving is the natural ability of the human body by involving various tissues such as bones, nerves, muscles, tendons and ligaments. The ability of motion is known as the Range Of Motion. In athletes the good ability of Range of Motion will certainly support athletic performance that affects their achievement. The unknown ability of Range of Motion and the effect of Proprioceptive Neuromuscular Facilitation stretching treatment carried out during the cooling down session on the Range of Motion of East Java Bank Junior volleyball players became the basis of the research. Objective: To determine the effect of providing Proprioceptive Neuromuscular Facilitation Stretching During Cooling Down Session on the Range of Motion of East Java Bank Junior volleyball players. Methods: In this study, a quantitative approach with the Pre-Experimental Designs was used using the form of the One Group Pretest-Posttest Designs. All players were involved in the study (population research), totaling 12 female players aged 13-19 years. The study began with a pretest, then continued with the treatment of Proprioceptive Neuromuscular Facilitation Stretch for 16 meetings and ended with posttest. Data retrieval uses a Range Of Motion measurement instrument with a Goniometer measuring instrument. Data analysis using the SPSS Statistics 19.0 application with the Paired Sample T-Test test to test the hypothesis. Results: Paired Sample T-Test results with a standard probability of 5% (based on Sig ? 0.05) indicate that the value based on Sig 16 of The 19 movements of the Range of Motion of the players measured have a Sig ? 0.05. Conclusion: Based on the results of the above research, the treatment of Proprioceptive Neuromuscular Facilitation Stretch which is carried out when Cooling Down Session influences the Range of Motion of East Java Bank Junior volleyball players. Keywords : proprioceptive neuromuscular facilitation stretching, cooling down, range of motion, East Java Bank Junior volleyball players, volleyball